Iron stress increases Bordetella pertussis mucin-binding capacity and attachment to respiratory epithelial cells - Pérez Vidakovics, María Laura Anabella (2007)
Whooping cough is a reemerging infectious disease of the respiratory tract caused by Bordetella pertussis. The incomplete understanding of the molecular mechanisms of host colonization hampers the efforts to control this disease. Among the environmental factors that commonly determine the bacterial phenotype, the concentration of essential nutrients is of particular importance. Iron, a crucial and scarce nutrient in the natural environment of B. pertussis, has been found to induce substantial phenotypic changes in this pathogen. However, the relevance of this phenotype for the interaction with host cells was never investigated. Using an in vitro model for bacterial attachment, it was shown that the attachment capacity of B. pertussis to epithelial respiratory cells is enhanced under iron stress conditions. Attachment is mediated by iron-induced surface-exposed proteins with sialic acid-binding capacity. The results further suggest that some of these iron-induced surface-associated proteins are immunogenic and may represent attractive vaccine candidates.